Blockade of Y177 and Nuclear Translocation of Bcr-Abl Inhibits Proliferation and Promotes Apoptosis in Chronic Myeloid Leukemia Cells - Li, Qianyin (Int J Mol Sci, 2017)
The gradual emerging of resistance to imatinib urgently calls for the development of new therapy for chronic myeloid leukemia (CML). The fusion protein Bcr-Abl, which promotes the malignant transformation of CML cells, is mainly located in the cytoplasm, while the c-Abl protein which is expressed in the nucleus can induce apoptosis. Based on the hetero-dimerization of FKBP (the 12-kDa FK506- and rapamycin-binding protein) and FRB (the FKBP-rapamycin binding domain of the protein kinase, mTOR) mediated by AP21967, we constructed a nuclear transport system to induce cytoplasmic Bcr-Abl into nuclear. In this study, we reported the construction of the nuclear transport system, and we demonstrated that FN3R (three nuclear localization signals were fused to FRBT2098L with a FLAG tag), HF2S (two FKBP domains were in tandem and fused to the SH2 domain of Grb2 with an HA tag) and Bcr-Abl form a complexus upon AP21967. Bcr-Abl was imported into the nucleus successfully by the nuclear transport system. The nuclear transport system inhibited CML cell proliferation through mitogen-activated protein kinase (MAPK) and signal transducer and activator of transcription 5 (STAT5) pathways mainly by HF2S. It was proven that nuclear located Bcr-Abl induced CML cell (including imatinib-resistant K562G01 cells) apoptosis by activation of p73 and its downstream molecules. In summary, our study provides a new targeted therapy for the CML patients even with Tyrosine Kinase Inhibitor (TKI)-resistance.